Komunikasi simbolik kelompok Gay Semarang - Pudrianisa, Sheila Lestari Giza (Faculty of Communications Science, Dr. Soetomo University, 2022)
LBHM survey on 2019 mentioned that LGBT groups often experience stigma and discrimination. Although it is widely discussed, it is not easy to access information about these groups. Thus, the problem focuses on how the Semarang gay group uses symbolic communication so that the public can see the symbols used by the Semarang gay group to interact and communicate. This research uses a constructivism paradigm with the qualitative descriptive method and Symbolic Convergence as the main theory. As a result, fantasy exchange creates various communication symbols that converge in the form of verbal (effeminate language/oral and written) and non-verbal (object language, action language and sign language) and are mutually agreed upon as identities to form group cohesiveness. Bad experiences such as stigma/discrimination are the basis for creating safe and easy-to-understand communication symbols between members in exchanging messages and meanings that become the group's motives.